The role of CYP2C19*2 variant and other factors in clopidogrel resistance in Montenegrin ACS patients - Svetlana Perović; Slavica Vujović; Saša Perović; Anđelka Šćepanović (Genetics & Applications)
Clopidogrel, an antiplatelet drug, has been widely prescribed for the treatment of acute coronary syndrome (ACS) for over two decades. Despite the fact that the drug proved to be effective in the majority of patients, in some, due to an inadequate response, the recurrence of adverse cardiovascular events represents a significant problem. These interindividual differences in response to clopidogrel may be due to genetic variations, concomitant therapy and associated diseases. The purpose of this study is to examine the association of the CYP2C19*2 loss of function variant, as well as other variables such as demographic characteristics, concomitant diseases and therapy with resistance, i.e. reduced drug efficacy in the Montenegrin cohort. The study included a total of 196 patients diagnosed with ACS who were on clopidogrel therapy. Patients were monitored for a one- year period, after the introduction of therapy, and divided into two groups: effective and ineffective clopidogrel therapy group. Genotyping for the CYP2C19*2 variant was performed using the real-time qPCR method. Our results show that atrial fibrillation (AF) is associated with impaired efficacy of clopidogrel in reducing the occurrence of adverse CV events during one year after the diagnosis of ACS (p = 0.040). There was no statistically significant difference between the effective and ineffective therapy group concerning CYP2C19*2 allele and genotype distribution (p = 0.438, p = 0.328) respectively. In conclusion, our findings indicate that AF could be potential non-genetic cause of ineffective clopidogrel therapy in ACS patients.